2019
DOI: 10.1038/s41598-019-52278-3
|View full text |Cite|
|
Sign up to set email alerts
|

The HIV protease inhibitor darunavir prevents kidney injury via HIV-independent mechanisms

Abstract: HIV-associated nephropathy (HIVAN) is a rapidly progressive kidney disease that is caused by HIV infection of renal epithelial cells with subsequent expression of viral genes, including vpr. Antiretroviral therapy ameliorates HIVAN without eradicating HIV from the kidneys and the mechanism by which it protects kidneys is poorly understood. Since HIV protease inhibitors have “off target” cellular effects, we studied whether darunavir, the most commonly prescribed protease inhibitor, protects kidneys from HIV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…[9] Moreover, Gao X et al demonstrated that darunavir has a protective effect against HIV-induced renal injury by reducing albuminuria and kidney injury and suppressing HIV-induced upregulation of immune response genes in human kidney cells. [10] Based on a cross-sectional study published by de Lastours et al in 2013, 4 out of 51 HIV patients who received a DRV-based regimen developed high levels of DVR crystals in urine, and the author concluded that DVR potential renal toxicity should be considered. [11] Risk factors that can increase the risk of developing AKI in patients on ART therapy include diabetes mellitus, hypertension, nephrotoxic drug intake, preexisting kidney disease, older age, elevated baseline creatinine level, female gender and African American ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Moreover, Gao X et al demonstrated that darunavir has a protective effect against HIV-induced renal injury by reducing albuminuria and kidney injury and suppressing HIV-induced upregulation of immune response genes in human kidney cells. [10] Based on a cross-sectional study published by de Lastours et al in 2013, 4 out of 51 HIV patients who received a DRV-based regimen developed high levels of DVR crystals in urine, and the author concluded that DVR potential renal toxicity should be considered. [11] Risk factors that can increase the risk of developing AKI in patients on ART therapy include diabetes mellitus, hypertension, nephrotoxic drug intake, preexisting kidney disease, older age, elevated baseline creatinine level, female gender and African American ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…O Darunavir é um inibidor de protease de segunda geração aprovado para o tratamento inicial de pacientes com HIV, bem como para aqueles que possuam a doença há mais tempo e que resistem a outros inibidores de proteases (41). O Darunavir deve ser administrado com alimentação para aumentar a sua absorção e é biotransformado intensamente pelas CIP3A4 (42).…”
Section: Darunavirunclassified
“…However, when ART is employed along with the close monitoring of kidney function, it has been shown to effectively manage HIV-associated kidney disease. Importantly, studies have shown that effective treatment with ART decreases the morbidity and mortality in patients with HIV-associated kidney diseases and also the progression to ESKD [9,17,20], though the exact mechanisms by which ART ameliorates kidney disease are not yet clear [10], .…”
Section: Introductionmentioning
confidence: 99%